2020
DOI: 10.1038/s41598-020-68439-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new regulatory genes through expression pattern analysis of a global RNA-seq dataset from a Helicobacter pylori co-culture system

Abstract: Helicobacter pylori is a gram-negative bacterium that persistently colonizes the human stomach by inducing immunoregulatory responses. We have used a novel platform that integrates a bone marrowderived macrophage and live H. pylori co-culture with global time-course transcriptomics analysis to identify new regulatory genes based on expression patterns resembling those of genes with known regulatory function. We have used filtering criteria based on cellular location and novelty parameters to select 5 top lead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
0
11
1
Order By: Relevance
“…The function of our key gene in EMT may indicate that PLXDC2 is a regulator of tumor metastasis. It has also been reported that deficiency of PLXDC2 suppresses the bacterial colonization of HP infection (Tubau-Juni et al, 2020). In our studies, however, we discovered no clear evidence that the expression level of PLXDC2 may influence HP infection in GC (Supplementary Figure 2).…”
Section: Discussioncontrasting
confidence: 75%
“…The function of our key gene in EMT may indicate that PLXDC2 is a regulator of tumor metastasis. It has also been reported that deficiency of PLXDC2 suppresses the bacterial colonization of HP infection (Tubau-Juni et al, 2020). In our studies, however, we discovered no clear evidence that the expression level of PLXDC2 may influence HP infection in GC (Supplementary Figure 2).…”
Section: Discussioncontrasting
confidence: 75%
“…S4A). Genes upregulated in Fb MME include Lama2 (loss is associated with muscular dystrophy ( 39 )), Plxdc2 (inflammation suppressor ( 40 )), and Cxcl14 , (implicated in chemotaxis ( 41 )). Downregulated genes in e23AON-treated mdx Fb MME include Sparc, Meg3 and collagens, Col3a1, Col1a1 , and Col1a2 , which have been implicated in inflammation or fibrosis (Datafile S3, Table S1d, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Host colonization, tolerance induction, and induction of immunoregulatory response require the role of the macrophage peroxisome proliferator-activated receptor gamma (PPARγ), an anti-inflammatory transcription factor [ 45 ]. These results suggest that Hp might represent a suitable system to identify the regulatory mechanisms controlling the host immune response [ 46 ].…”
Section: Potential Role Of Hp Against Inflammamentioning
confidence: 99%
“…In vitro cocultures of a wild type or of PPARγ-deficient bone-marrow-derived macrophages with live Hp identified several potential new immunoregulatory genes. One of them (Plexin domain-containing 2; Plxdc2 ) was confirmed to play an immunoregulatory role in the Hp infection, in a mouse model of inflammatory bowel disease, and potentially in other inflammatory and autoimmune diseases [ 46 ].…”
Section: Potential Role Of Hp Against Inflammamentioning
confidence: 99%